The reservoir tapes - McGregor, Jon, 1976- (Catapult, 2018)
"A teenage girl has gone missing. The whole community has been called upon to join the search. And now an interviewer arrives, intent on capturing the community's unstable stories about life in the weeks and months before Becky Shaw vanished"--